2017
DOI: 10.1103/physrevc.96.054305
|View full text |Cite
|
Sign up to set email alerts
|

Effective proton-neutron interaction near the drip line from unbound states in F25,26

Abstract: Background: Odd-odd nuclei, around doubly closed shells, have been extensively used to study proton-neutron interactions. However, the evolution of these interactions as a function of the binding energy, ultimately when nuclei become unbound, is poorly known. The 26 F nucleus, composed of a deeply bound π 0d 5/2 proton and an unbound ν0d 3/2 neutron on top of an 24 O core, is particularly adapted for this purpose. The coupling of this proton and neutron results in a J π = 1 1 + − 4 1 + multiplet, whose energie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 57 publications
(195 reference statements)
2
18
0
Order By: Relevance
“…The spectrum of 26 F is presented in Figure 4 and compared to experimental data [19,20]. Considering the new shell closure discovered with 24 O [3,4], 26 F can simply be treated as one Excitation Energy (MeV) 26 F Figure 4: Energy spectrum for 26 F calculated with MPBT+GSM and compared with experimental data [19,20] and other calculations where continuum coupling is discarded: SM with USDB interaction and VS-IMSRG with NN+3NF.…”
Section: Calculations and Discussionmentioning
confidence: 99%
“…The spectrum of 26 F is presented in Figure 4 and compared to experimental data [19,20]. Considering the new shell closure discovered with 24 O [3,4], 26 F can simply be treated as one Excitation Energy (MeV) 26 F Figure 4: Energy spectrum for 26 F calculated with MPBT+GSM and compared with experimental data [19,20] and other calculations where continuum coupling is discarded: SM with USDB interaction and VS-IMSRG with NN+3NF.…”
Section: Calculations and Discussionmentioning
confidence: 99%
“…Recently, significant attention has been given to a dripline nucleus 26 F [59,62]. The low-energy theoretical spectra of 26 F are shown in Fig.…”
Section: Fmentioning
confidence: 99%
“…If one assumes that, as in the independent particle picture, the low-energy multiplet of states (1 + −4 + ) is mainly provided by (πd 5/2 )(νd 3/2 ) configuration, then one can estimate empirical protonneutron matrix elements as proposed in Refs. [59,62],…”
Section: Fmentioning
confidence: 99%
“…Christian et al [10] found that 28 F is unbound by 220(50) keV, and based on the agreement with the predictions of USDA/USDB shell-model calculations 28 F was placed outside the "Island of Inversion" (IoI) [11]. This means that the ground state of 28 F could be described by a particle-hole configuration (π0d 5/2 × ν0d −1 3/2 ) with respect to an unbound core of 28 O, forming a multiplet of J π = 1 + -4 + states as in 26 F [12,13]. On the other hand, the relatively low energies of the first excited states in 27,29 F suggest the presence of intruder neutron pf -shell contributions [14].…”
Section: Pacs Numbersmentioning
confidence: 90%
“…The first positive-parity states are predicted too low in energy, which could be explained by effects of the continuum (not taken into account explicitly in the present calculations) that change the effective two-body matrix elements [13,56] and induce lingering of the ℓ = 1 states compared to ℓ = 2 [8]. Another feature that could be related to the effects of the continuum, discussed in Ref.…”
Section: Pacs Numbersmentioning
confidence: 91%